2019
DOI: 10.1002/ijc.32321
|View full text |Cite
|
Sign up to set email alerts
|

MKK7 transcription positively or negatively regulated by SP1 and KLF5 depends on HDAC4 activity in glioma

Abstract: JNK activity has been implicated in the malignant proliferation, invasion and drug‐resistance of glioma cells (GCs), but the molecular mechanisms underlying JNK activation are currently unknown. Here, we reported that MKK7, not MKK4, directly activates JNK in GCs and exerts oncogenic effects on tumor formation. Notably, MKK7 expression in glioma tissues was closely correlated with the grade of the glioma and JNK/c‐Jun activation. Mechanistically, MKK7 transcription critically depends on the complexes formed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…The luciferase reporter assay confirmed the target relationship between miR-152 and KLF5, as well as MKK7. Interestingly, the transcriptional factor KLF5 has been demonstrated to positively regulate MKK7 expression by binding with MKK7 promoter regions [11]. Our findings also indicate that MKK7 transcription was promoted by KLF5.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The luciferase reporter assay confirmed the target relationship between miR-152 and KLF5, as well as MKK7. Interestingly, the transcriptional factor KLF5 has been demonstrated to positively regulate MKK7 expression by binding with MKK7 promoter regions [11]. Our findings also indicate that MKK7 transcription was promoted by KLF5.…”
Section: Discussionsupporting
confidence: 60%
“…These data suggested that miR-152 suppressed KLF5 and MKK7 expressions via targeting the 3'UTR of their mRNAs. In addition, a previous study has revealed that the tran-scriptional factor KLF5 could positively regulate MKK7 expression by binding with MKK7 promoter regions [11]. In our study, the overexpression of KLF5 in 5637 and T24 cells significantly induced the mRNA expression of MKK7 ( p < 0.01, Figure 3F ).…”
Section: Mir-152 Regulates Klf5 and Mkk7 Expressions By Targeting Thesupporting
confidence: 69%
See 2 more Smart Citations
“…The encoded protein is involved in many cellular processes, including cell differentiation, cell growth, apoptosis, immune responses, response to DNA damage, and chromatin remodeling. According to reports, SP1 plays important role in the tumorigenesis, progression, and drug resistance of gliomas [22][23][24][25]. We found that the promoter region of miR-4310 also contains GC-rich fragments.…”
Section: Sp1 Induces the Expression Of Mir-4310 By Binding To Its Promentioning
confidence: 77%